(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
From past few decades watermarking became very crucial for digital images being transmitted over network. All the time ownership and license are great issues if someone fetches the image sent by one without any ownership seal, i.e. watermark, and uses as his own image. In this paper the basic concept of watermarking is discussed and target focus is given to ellipse watermark. As circle is a special figure of ellipse and this paper applies ellipse watermark and verifies the fact that it matches the features of circle.